2007
DOI: 10.1111/j.1365-2664.2007.01393.x
|View full text |Cite
|
Sign up to set email alerts
|

Indicators for biodiversity in agricultural landscapes: a pan‐European study

Abstract: Summary 1.In many European agricultural landscapes, species richness is declining considerably. Studies performed at a very large spatial scale are helpful in understanding the reasons for this decline and as a basis for guiding policy. In a unique, large-scale study of 25 agricultural landscapes in seven European countries, we investigated relationships between species richness in several taxa, and the links between biodiversity and landscape structure and management. 2. We estimated the total species richnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
289
3
15

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 595 publications
(349 citation statements)
references
References 60 publications
20
289
3
15
Order By: Relevance
“…Landscape metric parameters such as the number and size of NSN landscape elements, which indicate the inteniForest 11: 491-498 493 sity of fragmentation, define the value of biodiversity at the landscape level (Fahrig 2003). The size metric of landscape elements strongly correlates with "species richness and the occurrence and abundance of some species" (McGarigal & Marks 1995) and can be interpreted as a spatial indicator of the biodiversity level (Billeter et al 2008, Kumar et al 2006). However, this metric has several limitations, among which is that it cannot illustrate spatial properties and the distribution of elements across the analysed landscape (Botequilha Leitao et al 2006).…”
Section: Theoretical Background Of Connectivity As a Multifunctional mentioning
confidence: 99%
“…Landscape metric parameters such as the number and size of NSN landscape elements, which indicate the inteniForest 11: 491-498 493 sity of fragmentation, define the value of biodiversity at the landscape level (Fahrig 2003). The size metric of landscape elements strongly correlates with "species richness and the occurrence and abundance of some species" (McGarigal & Marks 1995) and can be interpreted as a spatial indicator of the biodiversity level (Billeter et al 2008, Kumar et al 2006). However, this metric has several limitations, among which is that it cannot illustrate spatial properties and the distribution of elements across the analysed landscape (Botequilha Leitao et al 2006).…”
Section: Theoretical Background Of Connectivity As a Multifunctional mentioning
confidence: 99%
“…A number of studies identified positive relations between numbers of species and area of semi-natural habitat (Bruun 2000;Steffan-Dewenter and Tscharntke 2001;Kremen et al 2002;Dormann et al 2007;Hendrickx et al 2007;Billeter et al 2008). For instance, Billeter et al (2008) analysed the share of natural elements (% area) in 25 agricultural landscapes distributed across seven European countries (France, Belgium, the Netherlands, Germany, Switzerland, Czech Republic and Estonia), and concluded that the largest contribution to total species richness of vascular plants, birds and five arthropod groups comes from natural and semi-natural habitats and is directly influenced by their area in most agricultural landscapes.…”
Section: Assessing Pressures On Biodiversity At Landscape Leveltransfmentioning
confidence: 99%
“…At farm and landscape levels many studies (e.g. Herzog et al 2006;Billeter et al 2008;Kleijn et al 2009) have been based on empirical species abundance data. At higher levels using cause-effect relationships is a major approach (e.g.…”
Section: Biodiversity Assessment Approachesmentioning
confidence: 99%
See 2 more Smart Citations